Phosphorylated Nitrate Reductase and 14-3-3 Proteins : Site of Interaction, Effects of Ions, and Evidence for an AMP-Binding Site on 14-3-3 Proteins - Athwal, Gurdeep S. (American Society of Plant Physiologists, 1998)
The inactivation of phosphorylated nitrate reductase (NR) by the binding of 14-3-3 proteins is one of a very few unambiguous biological functions for 14-3-3 proteins. We report here that serine and threonine residues at the +6 to +8 positions, relative to the known regulatory binding site involving serine-543, are important in the interaction with GF14ω, a recombinant plant 14-3-3. Also shown is that an increase in ionic strength with KCl or inorganic phosphate, known physical effectors of NR activity, directly disrupts the binding of protein and peptide ligands to 14-3-3 proteins. Increased ionic strength attributable to KCl caused a change in conformation of GF14ω, resulting in reduced surface hydrophobicity, as visualized with a fluorescent probe. Similarly, it is shown that the 5′ isomer of AMP was specifically able to disrupt the inactive phosphorylated NR:14-3-3 complex. Using the 5′-AMP fluorescent analog trinitrophenyl-AMP, we show that there is a probable AMP-binding site on GF14ω.